Effect of Moisture Content on Physical and Frictional Properties of Pearl Millet (Pennisetum glaucum) Seed - Patel, Naveendra Kumar; Yadav, Rahul Kumar; Mishra, Abhishek; Kumar, Sunil (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during the month of August, 2025 at the Dept. of Agril. Engg., SKNAU, Rajasthan, India, to study the effect of moisture content on physical and frictional properties of pearl millet (Bajra). The physical and frictional properties of pearl millet were determined at moisture contents ranging from 8.82% to 16.3%. The average values of length, breadth, and thickness for the RHB-223 variety of pearl millet were found to be 3.135, 1.89, and 1.39 mm, respectively. The average values of geometric, arithmetic, square and equivalent mean diameter of RHB-223 were observed to be 2.02, 2.14, 3.59 and 2.58 mm, respectively. The average data of surface area and volume for the RHB-223 variety were recorded as 14.42 mm2 and 8.34 mmn3 respectively. It was also observed that the average thousand seed weight of the pearl millet variety RHB-223 was 9.258 g. The average data of bulk density, true density and density ratio for the RHB-223 variety were found to be 687.558 kg m-3 and 1045.273 kg m-3 and 0.658 respectively. It was also observed that the average porosity of the pearl millet variety RHB-223 was 34.222. The average value of angle of repose for the RHB-223 variety was recorded as 27.943º. The average coefficient of static friction for pearl millet variety RHB-223 on plastic, MS sheet and plywood surface was found to be 0.384, 0.438, 0.513 respectively.